ANALISIS KUALITAS LAYANAN PADA TOUR DAN TRAVEL DI BANYUWANGI INDONESIA - Yuda Teguh Siswanto; Dwi Cahyono; Abadi Sanosra (Economos : Jurnal Ekonomi dan Bisnis, 2022)
Tourism in Banyuwangi is very diverse and attracts the attention of local and foreign tourists, especially tourist attractions that have extraordinary beauty. Tourist attractions that are currently in demand by local and foreign tourists are Ijen crater, Plengkung beach, and the beach. Sukomad. The purpose of this study was to determine directly or indirectly the effect of service quality, and price on interest by referring to customer satisfaction as an intervening variable on tour & travel in Banyuwangi Regency. The number of samples in this study was 170 using the purposive sampling technique. The analysis technique used Structural Equation Model (SEM) using Warp PLS7.0. The results of data analysis show that (1) service quality has a significant effect on interest in referring, (2) price has a significant effect on interest in referring, (3) service quality and price have a significant effect on interest in referring through customer satisfaction as an intervening variable